Influence of Physicochemical Properties of Oil Sludge on Syngas Production for Energy Applications - Hiago Oliveira; Isabela Pinheiro; Ana Ramos; Osvaldo Venturini; Adriano Mariano; York Santiago (Resources)
Oil sludge (OS) is a hazardous waste generated in the refinery and platform production chain. Its recovery is globally limited by methods like incineration, landfilling, and stabilization, which are costly and environmentally harmful. In Brazil, advanced techniques such as gasification are still underdeveloped compared to established practices elsewhere. This study aims to characterize the chemical and physical properties of OS to enable its recovery through energy methods, reducing environmental impacts. OS samples from oil storage tanks were analyzed using mass spectrometry, thermogravimetry, atomic absorption, proximate analysis, X-ray fluorescence, and X-ray diffraction. The viscosity was approximately 34,793 cP, with 36.41% carbon and 56.80% oxygen. The ash content was 43.218% (w/w), and the lower and upper heating values were 17.496 and 19.044 MJ/kg, respectively. Metal analysis identified lead, vanadium, manganese, and chromium. The high ash content of OS reduced gasification temperatures, increasing char yield (44.6%). Increasing the equivalence ratio (ER) led to higher gasification temperatures, producing energetic species such as H2, CH4, and CO, raising the calorific value of the resulting syngas. Subsequently, this syngas was used in gas turbine models with GasTurb software 14.0, achieving electrical output and thermal efficiency of 66.9 kW and 22.4%, respectively. OS is a persistent waste requiring gasification treatment, offering a promising solution that converts these residues into valuable syngas for energy conversion with minimal environmental impact.